Human herpesvirus 6B infection in an adult with hemophagocytic lymphohistiocytosis carrying an UNC13D mutation: a case report and literature review - Xiao, Pingping; Wang, Qingqing; Li, Tingting; Dong, Zhigao; Su, Junnan; Chen, Yongquan (Frontiers in Immunology, 2025)
Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening hyperinflammatory syndrome. The cause of onset broadly distinguishes primary from acquired HLH. However, an increasing number of carrying HLH gene mutation cases have been reported in adults, and the relationship between genetic alterations and the onset of HLH in adults is still being explored. In this case, a 43-year-old woman with a one-month history of abnormal liver function and fever presented for evaluation. Laboratory data indicated pancytopenia, elevated ferritin levels, decreased fibrinogen levels, and the presence of phagocytes in the bone marrow. She was diagnosed with HLH and found to have a heterozygous mutation in the UNC13D gene. The onset of symptoms in this patient coincided with the exacerbation of human herpesvirus 6B infection. From our review of case reports published in the past seven years, patients with HLH carrying this heterozygous gene mutation were diagnosed in adults. The patient remains alive and healthy after comprehensive treatment. The genetic background must not be overlooked in the etiological diagnosis of adult hemophagocytic lymphohistiocytosis, even in the presence of infectious pathogenic factors. Future studies need to be undertaken involving a larger number of cases, along with virology and genomics correlation.